The everyday Atlantic : time, knowledge, and subjectivity in the twentieth-century Iberian and Latin American newspaper chronicle - Gentic, Tania, 1978- (SUNY series in Latin American and Iberian thought and culture, 2013)
"Rethinks the concepts of nation and community in Spain and Latin America by examining the everyday writing of the newspaper chronicle and blog"--Provided by publisher.